Sistem Kelembagaan Organisasi Subak Sebagai Pengelola Sumber Daya Air Berkelanjutan - Diah Astriani Putri S.; Rachmad K. Dwi Susilo; Muhammad Hayat; Joan Hesti Gita Purwasih (Universitas Lambung Mangkurat, 2020)
Subak Babakan Bayu is a social institution that is in the midst of growth in Bali’s tourism industry, but Subak Babakan Bayu is able to maintain its existence as an executor of ritual activities, irrigation water management, buffering food security, environmental preservation and culture in a sustainable manner. The purpose of this research is to understand the organizational system of Subak Babakan Bayu. This research is a qualitative study using an ethnographic approach. The research location was in Sangkaragung Village, Jembrana District, Jembrana Regency, Bali. Data collection techniques using observation, interviews, and documentation. The technique of determining the subject of research using purposive sampling and using data analysis techniques include domain analysis, taxonomic analysis, compound analysis, and cultural theme analysis. The theory used is the social system theory from Niklass Luhmann and the new institutional theory (new institutional theory) from William Richard Scott. The results of this study indicate that the organizational system of the Subak Babakan Bayu organization has three basic elements that make the subak institution strong, namely the regulatory system including awig-awig, and perarem. The normative system is the norm of responsibility and justice, and the cognitive cultural system that includes beliefs, traditions and rituals. In its implementation, there are some obstacles but the social system is able to heal itself so that Subak Babakan Bayu still exists.